Some biochemical changes during the fermentation of lupine (Lupinus luteus L.) silages - Buys, Gerhardus Stefanus (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1964.